Typifications and taxonomical rearrangements in North and Central American Tagetes (Asteraceae, Tageteae) - Schiavinato, Dario J.; Gutiérrez, Diego G.; Bartoli, Adriana (Phytotaxa, 2021)
During the revision of the genus Tagetes, we detected the need for typifications and taxonomical rearrangements in North and Central American taxa. We analyzed type and non-type specimens, morphological traits, geographical distributions, protologues, and biographies of authors and collectors. As a result, we designated 12 lectotypes and one epitype for the following plant names: T. clandestina, T. florida, T. lemmonii, T. lucida, T. macroglossa, T. micrantha, T. nelsonii, T. oligocephala, T. schiedeana, T. signata, T. signata var. pumila and T. triradiata. In addition, we placed T. oligocephala in synonymy within T. foetidissima and clarified type localities of T. oligocephala and T. schiedeana.